Danhong injection alleviates cerebral ischemia-reperfusion injury by inhibiting autophagy through miRNA-132-3p/ATG12 signal axis. (10th January 2023) - Zhang, Hongrui; Wang, Xinyi; Chen, Weiwei; Yang, Yixuan; Wang, Yu; Wan, Haitong; Zhu, Zhenhong
Abstract: Ethnopharmacological relevance: Danhong injection (DHI) is a renowned traditional Chinese medicine often used clinically to treat cardiovascular and cerebrovascular diseases. Studies have shown that DHI can significantly alter microRNA (miRNA) expression in the brain tissue. Therefore, exploring specific miRNAs' regulatory mechanisms during treatment with DHI is essential. Aim of the study: To investigate DHI's regulatory mechanism on cerebral autophagy in rats with cerebral ischemia-reperfusion injury (CIRI). Material and methods: Rats were randomly divided into the sham, middle cerebral artery occlusion (MCAO) model, and DHI-treatment groups. The extent of brain damage was evaluated using triphenyl tetrazolium chloride and hematoxylin-eosin staining. Hippocampal cell autophagy was observed using transmission electron microscopy. Autophagy-related proteins were analyzed using western blotting. Differentially expressed miRNAs were screened using high-throughput and real-time quantitative reverse transcription PCR. The relationship between miR-132-3p and ATG12 was confirmed using a dual-luciferase assay. The miR-132-3p mimics and inhibitors were transfected into PC12 cells subjected to oxygen-glucose deprivation (OGD) in vitro and MCAO model rats in vivo. Results: DHI significantly altered the miRNA expression profile in rat brain tissues. The pathological changes in the brain tissues were improved, and the autophagic hippocampal cell vehicles were significantly reduced after DHI treatment. miRNA-132-3p, one of the miRNAs with a significantly different expression, was screened. Kyoto Encyclopedia of Genes and Genomes signal pathway analysis showed that its target genes were closely related to autophagy. Western blotting revealed that the p-PI3K, p-AKT, and mTOR expression increased significantly; AMPK, ULK1, ATG12, ATG16L1, and LC3II/I were downregulated in the DHI group. Dual-luciferase reporter gene experiments showed that miRNA-132-3p could target the ATG12 3′-UTR region directly. In vitro, miRNA-132-3p had a protective effect on OGD/R-induced oxidative stress injury in PC12 cells, improving cell viability, and affecting the expression of autophagy pathway-related proteins. In vivo transfection experiments showed that miR-132-3p could regulate ATG12 expression in CIRI rats' lateral brain tissue, affecting the autophagy signaling pathway. miR-132-3p overexpression reduces CIRI-induced autophagy and protects neurons. Conclusion: This study showed that DHI inhibits neuronal autophagy after cerebral ischemia-reperfusion. This may have resulted from miR-132-3p targeting ATG12 and regulating the autophagy signaling pathway protein expression. Graphical abstract: Image 1 Highlights: Danhong injection (DHI) is a renowned traditional Chinese medicine. DHI can significantly change the miRNA expression profile of brain tissue. DHI can inhibit the production of autophagy-related proteins. CIRI is a complex pathophysiological process involving multiple mechanisms.